2020
DOI: 10.1002/ange.202001589
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Dithionite‐Mediated Decarboxylative Sulfonylation: Facile Access to Tertiary Sulfones

Abstract: A straightforward multicomponent decarboxylative cross coupling of redox‐active esters (N‐hydroxyphthalimide ester), sodium dithionite, and electrophiles was established to construct sterically bulky sulfones. The inorganic salt sodium dithionite not only served as the sulfur dioxide source, but also acted as an efficient radical initiator for the decarboxylation. Notably, diverse naturally abundant carboxylic acids and artificially prepared carboxyl‐containing drugs with multiple heteroatoms and sensitive fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…In view of its unique potential as single-electron reductant 55 , sodium dithionite was employed as the sulfur dioxide surrogate in combination with diazonium salts in our initial design to generate sulfonyl radicals for initiating the rearrangement. Using N -arylsulfinyl acrylamide 1a and aryldiazonium salt 2a as model substrates, we commenced the search for suitable reaction conditions with the corresponding results outlined in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In view of its unique potential as single-electron reductant 55 , sodium dithionite was employed as the sulfur dioxide surrogate in combination with diazonium salts in our initial design to generate sulfonyl radicals for initiating the rearrangement. Using N -arylsulfinyl acrylamide 1a and aryldiazonium salt 2a as model substrates, we commenced the search for suitable reaction conditions with the corresponding results outlined in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, one feasible way is to activate the carboxylic acids and alkyl primary amines to the corresponding redox-active esters (RAE) and Katritzky's N-alkylpyridinium salts, respectively 16,17 . Previous studies demonstrated that both RAE [18][19][20][21][22][23][24][25][26][27][28] and Katritzky's salts [29][30][31][32][33][34][35][36][37] are predisposed to accept an electron from low-valent transition metals or organic Lewis bases under photocatalytic reaction conditions, thereby acting as precursors to the corresponding alkyl radicals (Fig. 1b) [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] .…”
mentioning
confidence: 99%
“…Thus, it can recognize the non‐ionic nitroolefin 115 [66d–h] through the H‐bond interaction to control the enantioselectivity. The catalyst of 2,6‐lutidine as Brønsted base can deprotonate the acidic nucleophile of thiol 116 , and then leading to realizing the asymmetric sulfa‐Michael addition and affording the desired sufide 117 [66i–t] . The diverse derivatization finally transfers the sulfide 117 to the bioactive molecules of taurine derivative 118 and 4‐monosubstituted β ‐sultam 119 .…”
Section: Asymmetric Reactions Catalyzed By Multi‐organocatalystsmentioning
confidence: 99%